5 - Development of Human Capital for Industrialisation: Drawing on the Experiences of Best Performers - Moyo, Theresa (Africa Development, 2018)
The experience of most industrialised countries indicate that part of their success was achieved through massive investment in developing human capacity, with particular focus on technical skills that are relevant for industry. Although Africa has a clear agenda to achieve the goal of an inclusive and transformative industrialisation, it has not been very successful in building the requisite skills base. To achieve its industrialisation goal as laid out in Agenda 2063, the Action Plan for the Industrial Development of Africa (AIDA) and the Sustainable Development Goals (SDGs) 2030, a more transformative approach to human capacity development must be a top priority. The continent can also draw lessons from high performers in industrialisation such as Germany, Singapore, Japan and the Republic of Korea. The article therefore examines the strategies that such countries have implemented to achieve success. It draws from the work of Friedrich List which argues that mental power or accumulation of knowledge and experience is the main element of productive power and industrialisation. A qualitative research methodology is applied.